PUCHI Regulates Giant Cell Morphology During Root-Knot Nematode Infection in Arabidopsis thaliana - Suzuki, Reira; Yamada, Mizuki; Higaki, Takumi; Aida, Mitsuhiro; Kubo, Minoru; Tsai, Allen Yi-Lun; Sawa, Shinichiro (Frontiers in Plant Science, 2021)
Parasitic root-knot nematodes transform the host’s vascular cells into permanent feeding giant cells (GCs) to withdraw nutrients from the host plants. GCs are multinucleated metabolically active cells with distinctive cell wall structures; however, the genetic regulation of GC formation is largely unknown. In this study, the functions of the Arabidopsis thaliana transcription factor PUCHI during GC development were investigated. PUCHI expression was shown to be induced in early developing galls, suggesting the importance of the PUCHI gene in gall formation. Despite the puchi mutant not differing significantly from the wild-type in nematode invasion and reproduction rates, puchi GC cell walls appeared to be thicker and lobate when compared to the wild-type, while the cell membrane sometimes formed invaginations. In 3D reconstructions of puchi GCs, they appeared to be more irregularly shaped than those in the wild-type, with noticeable cell-surface protrusions and folds. Interestingly, the loss-of-function mutant of 3-KETOACYL-COA SYNTHASE 1 (KCS1) showed GC morphology and cell wall defects similar to those of the puchi mutant, suggesting that PUCHI may regulate GC development via very long chain fatty acid synthesis.